Pengaruh Kompensasi CEO terhadap Penghindaran Pajak dengan Kualitas Audit Sebagai Variabel Moderasi: Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI pada Tahun 2019-2021 - Randa, Ridho Aulia; Helmy, Herlina (Universitas Negeri Padang, 2023)
This study examines the effect of CEO compensation on tax avoidance with audit quality as a moderating variable. This research is a type of causative research. The population in this study is the manufacturing industry sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The research sample was obtained using purposive sampling method which produced 120 observations. The results of this study explain that CEO compensation has no significant effect on tax avoidance practices. And audit quality cannot moderate or weaken the relationship between CEO compensation and tax avoidance. Subsequent research, using other audit quality measurements such as the Audit Quality Metric Score (AQMS), added other independent variables and added the research time span so that it would provide better results.